Principles of virology I - Condit, Richard (Henry Stewart Talks, 2007)
Viruses defined, History, Basic virus structure, Capsid symmetry, Properties of enveloped viruses, Properties of naked capsid viruses, Virus classification, Major diseases caused by human viruses, Virus replication, Virus growth, Viral pathogenesis, Entry, Replication and spread, Shedding, transmission, Disease patterns, Effects on cells, Emerging infections, Virus|host equilibrium, Factors influencing emergence
Archived at 2020/04/29